Eileen [videorecording (DVD)] - Goebel, Luke B., 1980-; Moshfegh, Ottessa; McKenzie, Thomasin, 2000-; Whigham, Shea, 1969-; Ireland, Marin; Teague, Owen, 1998-; Hathaway, Anne, 1982-; Moshfegh, Ottessa (Neon, 2024)
In 1960s Boston, Eileen shuffles between her emotionally haunted home and the prison where she works. When an intoxicating woman joins the prison staff, Eileen is taken but her newfound confidant entangles her in a shocking crime.